2010
DOI: 10.1111/j.1574-6968.2010.01910.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ACC deaminase from the biocontrol and plant growth-promoting agent Trichoderma asperellum T203

Abstract: 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity was evaluated in the biocontrol and plant growth-promoting fungus Trichoderma asperellum T203. Fungal cultures grown with ACC as the sole nitrogen source showed high enzymatic activity. The enzyme encoding gene (Tas-acdS) was isolated, and an average 3.5-fold induction of the gene by 3 mM ACC was detected by real-time PCR. Escherichia coli bacteria carrying the intron-free cDNA of Tas-acdS cloned into the vector pAlter-EX1 under the control of the tac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(127 citation statements)
references
References 26 publications
2
117
0
8
Order By: Relevance
“…However, plant growth promotion may also be mediated by a decrease in the levels of the plant hormone ethylene 93 . T. asperellum T203 (later re-classified as T. asperelloides) 20 possesses an α-1-aminocyclopropane-1-carboxylate (ACC) deaminase gene (acc1) that encodes an enzyme that cleaves ACC, a key intermediate in ethylene biosynthesis, and is expressed during interaction with roots of Brassica napus (canola) 94 . A knock-out in this gene reduced the ability of the fungus to promote root elongation.…”
Section: Promotion Of Plant Growthmentioning
confidence: 99%
“…However, plant growth promotion may also be mediated by a decrease in the levels of the plant hormone ethylene 93 . T. asperellum T203 (later re-classified as T. asperelloides) 20 possesses an α-1-aminocyclopropane-1-carboxylate (ACC) deaminase gene (acc1) that encodes an enzyme that cleaves ACC, a key intermediate in ethylene biosynthesis, and is expressed during interaction with roots of Brassica napus (canola) 94 . A knock-out in this gene reduced the ability of the fungus to promote root elongation.…”
Section: Promotion Of Plant Growthmentioning
confidence: 99%
“…Trichoderma spp. were reported have the ability to reduce several plant diseases by inhibiting plant pathogens mainly found in the soil roots, through antagonistic and mycoparasitic potential (Viterbo et al, 2010). For instance, studies conducted by Ha (2010) in Vietnam, indicated that Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%
“…Di samping dapat mengeluarkan metabolit sekunder (Mukherjee, Horwitz, Herrera-Estrella, Schmoll, & Kenerley, 2013;Vinale et al, 2014), beberapa jenis Trichoderma juga dapat berperan sebagai dekomposer untuk meningkatkan kesuburan tanah sehingga dapat memicu pertumbuhan tanaman (Kaewchai, Soytong, & Hyde, 2009;Contreras-Cornejo, Machias-Rodriguez, Cortẻs-Penagos, & Lỏpez-Bucio, 2009;Viterbo, Landau, Kim, Chernin, & Chet, 2010;Akladious & Abbas, 2012;Haque, Ilias, & Molla, 2012;Hermosa, Viterbo, Chet, & Lorito, 2012;Samolski, Rincỏn, Pinzỏn, Viterbo, & Monte, 2012;Promwee, Issarakraisila, Intana, Chamswarng, & Yenjit, 2014).…”
Section: Pendahuluanunclassified